The politics of law in late medieval and Renaissance Italy : essays in honour of Lauro Martines - Armstrong, Lawrin D. (Lawrin David); Kirshner, Julius; Martines, Lauro; Martines, Lauro (Toronto studies in medieval law., 2011)
"The Politics of Law in Late Medieval and Renaissance Italy features original contributions by international scholars on the fortieth anniversary of the publication of Lauro Martines' Lawyers and Statecraft in Renaissance Florence, which is recognized as a groundbreaking study challenging traditional approaches to both Florentine and legal history.